Faktor Risiko yang Berpengaruh terhadap Kejadian HIV/AIDS pada Laki-Laki Umur 25 - 44 Tahun di Kota Dili, Timor Leste - Maria Amelia; Suharyo Hadisaputro; Budi Laksono; Anies Anies (Jurnal Epidemiologi Kesehatan Komunitas, 2016)
Background: The development of HIV/AIDS epidemics in the world has led to a global problem and it is one of public health problems in East Timor. The age group of 25-44 years old is sexually active and productive group who needs to get a good review.Methods: This research used a case-control study design reinforced with qualitative data. The number of respondents was 112 respondents, including 56 cases (males with HIV/AIDS) and56 controls (males who did not suffer from HIV/AIDS). The research instruments were:questionnaires and interviews. The data analysis used univariate, bivariate (chi-square test)and multivariate (logistic regression test).Results: The variables proven to affect the prevalence of HIV/AIDS in males were age (OR =3.937; 95% CI = 1.564-9.908; p = 0.004), and alcohol consumption habits (OR = 7.658; 95%CI = 2.641-22.205 ; p = 0.0001). condom use (OR = 3.308; 95% CI = 1.469-7.450; p = 0.006) and access to localization (OR = 3.000; 95% CI = 1.348-6.678; p = 0.011). The variables which were not proven to be risk factors for the prevalence of HIV/AIDS were the level of education, knowledge, attitudes, promiscuous habits, drug use status, condom use, and socio- cultura.Conclusion: The risk factors proven to affect the prevalence of HIV/AIDS in males are age and alcohol consumption habits, the use of condoms and access to illegal localization. They are risky behaviors for HIV/AIDS with the probability of 63.02%.